The quasi-cooling effect of relativistic charged particles beams - Kulish, V.V.; Gubanov, I.V.; Nguen Ai Vent; Brusnik, A.J. (Вопросы атомной науки и техники, 2007)
A possibility of realization of a new, of principle, physical phenomenon is shown. This is the phenomenon of energy equalization of charged particle beams in the time their acceleration in the crossed undulative electric and magnetic fields (EH-fields). The phenomenon predicted is referred to as the quasi-cooling effect. Main properties and features of the effect are studied. In particular, it is shown that it would be experimentally observed for the existing today level of acceleration technologies.